Probiotic Saccharomyces boulardii Alleviates Lung Injury by Reduction of Oxidative Stress and Cytokine Response Induced by Supraceliac Aortic Ischemia-Reperfusion Injury in Rats - Durmaz,Selim (2021)
Abstract Objectives: Ischemia-reperfusion injury is an important cause of multiple organ failure in cardiovascular surgery. Our aim is to investigate the effect of the probiotic Saccharomyces boulardii on oxidative stress, inflammatory response, and lung injury in an experimental model of aortic clamping. Methods: Twenty-one Wistar rats were randomized into three groups (n=7). Control group animals received saline gavage for a week before undergoing median laparotomy. In other groups, supraceliac aorta was clamped for 45 minutes to induce ischemia followed by reperfusion for 60 minutes. In the ischemia-reperfusion group, saline gavage was given preoperatively for one week. Ischemia-reperfusion+probiotic group rats received probiotic gavage for seven days before aortic clamping. The levels of oxidative stress markers and pro-inflammatory cytokines were determined in both serum and lung tissue samples. Ileum and lung tissues were harvested for histological examination. Results: Ischemia-reperfusion caused severe oxidative damage and inflammation evident by significant increases in malondialdehyde and cytokine levels (tumor necrosis factor alpha and interleukin-1 beta) and decreased glutathione levels in both serum and lung tissues. There was severe histological tissue damage to the lung and ileum in the ischemia-reperfusion group. Probiotic pretreatment before aortic clamping caused significant suppression of increases in serum and lung tissue malondialdehyde and tumor necrosis factor alpha levels. Histological damage scores in tissue samples decreased in the ischemia-reperfusion+probiotic group (P<0,005). Conclusions: Oral supplementation of probiotic S. boulardii before supraceliac aortic ischemia-reperfusion in rats alleviates lung injury by reducing oxidative stress, intestinal cellular damage, and modulation of inflammatory processes.